Effectiveness of Manage Low-Quality Credit (Loan at Risk) for Improvement of Loan Portfolio Quality in Bank BNI - Angga Solissetiawan; Eliza Fatima (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Loan at Risk (LaR) is a problem faced by all banks where later if not managed properly and correctly it will become non-performing loans or reduce credit quality through increasing non-performing loans (NPL). The main purpose of this paper is to provide an evaluation of the effective LaR management strategy at Bank BNI for improving credit quality by improving the portfolio of LaR debtors in the period March 2020 to December 2021. For this purpose, we use primary data in the form of interviews with the parties involved and secondary data is the rules that serve as guidelines in managing LaR debtors. The results of the evaluation of the LaR management strategy are considered capable of improving credit quality through a decrease in the LaR portfolio.